The Development of a Website-Based Islamic Education Laboratory: Implementing Website-Based Islamic Education Learning at SMA Al-Islam Bandung - Fajar Farham Hikam (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2026)
The rapid evolution of Information and Communication Technology (ICT) has necessitated a digital transformation in Islamic Education (PAI). This study explores the development and implementation of a website-based PAI laboratory at SMA Al-Islam Bandung, an institution that utilizes virtual platforms to overcome the absence of physical laboratory facilities. Adopting a descriptive qualitative approach through field research, data were primarily collected via in-depth interviews with key informants, including specialized PAI educators. The findings indicate that the website-based laboratory serves as an effective virtual hub for disseminating instructional materials, broadcasting worship simulations, and managing digital assessments. The implementation has significantly improved student engagement and instructional flexibility; however, it faces technical hurdles such as bandwidth limitations and varying levels of device accessibility among students. The study concludes that while the virtual lab acts as a catalyst for modernizing PAI pedagogy, its success is highly contingent upon infrastructure stability and teacher digital literacy. This research provides a framework for integrating Islamic values with technological innovation to foster a more comprehensive and adaptive religious learning environment